Dialektika Sistem Peradilan Terhadap Analisis Kritis Perbandingan Litigasi Virtual dan Konvensional dalam Perspektif Hak Pembelaan Terdakwa - Yang Meliana (Jurnal Hukum Lex Generalis, 2025)
The development of information technology has introduced new dynamics in the judicial system through the implementation of virtual litigation as an alternative to conventional litigation. This study critically compares both systems from the perspective of the defendant’s right to defense. The findings indicate that virtual litigation provides efficiency and accessibility, yet faces challenges related to the principles of fair trial and defense effectiveness. Conversely, conventional litigation remains superior in physical presence and direct interaction. This study concludes that harmonizing both systems is essential to ensure the optimal protection of the defendant’s rights.